Korelasi Flow Mediated Dilation Brakial dengan Beratnya Stenosis Penyakit Arteri Koroner - Erwin Mulia; Ismoyo Sunu; Andang H Joesoef,; Ganesja M Harimurti (The Indonesian Heart Association, 2013)
Background. Endothelial dysfunction precedes the development of morphological changes and contributes to atherosclerotic lesion development and progression. Evaluation using non invasive method such as brachial FMD (flow mediated dilation) has given inconsistent information for extension and coronary atherosclerotic severity regarding endothelial dysfunction. This research will evaluate the correlation between brachial FMD and severity of coronary artery disease (CAD) stenosis.Methods. It was a cross sectional study. Evaluations were performed in 85 patients who had followed elective coronary angiography and fulfilled inclusion criteria in National Cardiovascular Center Harapan Kita since January until October of 2012. Correlation between brachial FMD and severity of CAD stenosis (Gensini score) was evaluated using linear regression analysis.Results. Brachial FMD had negative correlation with Gensini score (R= -0,227; P= 0,037). Hypertension had negative correlation with brachial FMD (R= -0,235; P= 0,032). Male gender had positive correlation with brachial FMD (R= 0,220; P= 0,040).Conclusion. There was weak negative correlation between brachial FMD and Gensini score.